Measurement of the Bs(0)→μ+ μ- branching fraction and search for B(0)→μ+ μ- with the CMS experiment. - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Erö, J.; Fabjan, C.; Friedl, M.; Frühwirth, R.; Ghete, V.; et al. (American Physical Society (APS), 2013)
Results are presented from a search for the rare decays B-s(0) -> mu(+) mu(-) and B-0 -> mu(+) mu(-) in pp collisions at root s = 7 and 8 TeV, with data samples corresponding to integrated luminosities of 5 and 20 fb(-1), respectively, collected by the CMS experiment at the LHC. An unbinned maximum-likelihood fit to the dimuon invariant mass distribution gives a branching fraction 'B(B-s(0) -> mu(+)mu(-)) = (3.0(-0.9)(+1.0)) x 10(-9), where the uncertainty includes both statistical and systematic contributions. An excess of B-s(0) -> mu(+)mu(-) events with respect to background is observed with a significance of 4.3 standard deviations. For the decay B-0 -> mu(+)mu(-) an upper limit of 'B(B-0 -> mu(+) mu(-)) < 1.1 x 10(-9) at the 95% confidence level is determined. Both results are in agreement with the expectations from the standard model.

Results are presented from a search for the rare decays Bs0→μ+μ- and B0→μ+μ - in pp collisions at √s=7 and 8 TeV, with data samples corresponding to integrated luminosities of 5 and 20 fb-1, respectively, collected by the CMS experiment at the LHC. An unbinned maximum-likelihood fit to the dimuon invariant mass distribution gives a branching fraction B(Bs0→μ+μ-)=(3.0-0.9+1.0) ×10-9, where the uncertainty includes both statistical and systematic contributions. An excess of Bs0→μ+μ- events with respect to background is observed with a significance of 4.3 standard deviations. For the decay B0→μ+μ- an upper limit of B(B0→μ+μ-)<1.1×10 -9 at the 95% confidence level is determined. Both results are in agreement with the expectations from the standard model.
Keywords: Physics; Physics Institute; Invariant mass distribution; B-MESON DECAYS; DENSITY-FUNCTION; Simulation; CMS, LHC, Bs0; High Energy Physics - Experiment; Tellurium compounds; Physics and Astronomy (all); p p collision; Large Hadron Collider; B-MESON DECAYS; CMS; B-MESON DECAYS; B-meson Decays; Standard deviation; Branching fractions; info:eu-repo/classification/ddc/530; Fisica delle particelle; Density-function; Integrated luminosity; CMS; Physics; ddc:530; Confidence levels; Física; Rare decays; p p collision; Upper limits; High Energy Physics - Phenomenology; The standard model; Large Hadron Collider; Simulation; Medicine (all); Physics and Astronomy (all); DENSITY-FUNCTION; standard deviation; Experiments; Simulation; Particle Physics - Experiment